Pengembangan Usaha dan Ekonomi Masyarakat Melalui BUMDES Munggaran - Nadila Fauziah; A. Bachrun Rifa’i (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2021)
The presence of Bumdes plays a role in developing the community's business and economy. In the last 6 years the number of Bumdes in Indonesia has continued to increase every year but its development is still diverse. This study aims to find out how the implementation, obstacles and success of the Munggaran Bumdes program in an effort to develop the business and economy of the community in Panumbangan Village. The method used in this research is descriptive qualitative with data collection techniques used are interviews, observations, and documentation studies. The results of the research in the field show that the Munggaran Bumdes has helped the community through capital assistance and business equipment, as well as providing training for both administrators and the community. In its implementation there are several obstacles such as lack of capital, limited knowledge of Bumdes management, lack of community participation. However, the benefits of the Bumdes Program can also be felt, marked by an increase in community income although it is not significant, the growth of group independence, and increasing public awareness related to efforts to improve the welfare of poor families around them.